Pengaruh Faktor Fundamental Mikro Makro terhadap Harga Saham Sektor Perbankan - Yuliarti Rezeki; Dyah Sri Wulandari; Linda Kusumawati (J-MAS (Jurnal Manajemen dan Sains), 2022)
Micro and macroeconomic fundamentals can affect the company's stock price. This is the background of this research. The objective is to analyze the microeconomic fundamentals, which consist of ROA, EPS, DER and macroeconomic fundamentals, namely inflation, Exchange and BI Rate against stock prices. The analytical method used is multiple linear regression with a population of 13 companies listed on the Stock Exchange and have met the sample criteria. Data in the form of banking financial reports for 2015-2019 and other data were obtained from Bank Indonesia, the Central Bureau of Statistics, and the Indonesian Stock Exchange. The results of the f test conclude that the micro and macroeconomic variables have a significant effect. The results of the t-test are only the ROA, DER and BI-Rate variables which are significant while the EPS, inflation, and exchange rate variables are not significant. The conclusion of this research for investors can consider ROA and DER variables as a measure of company performance. The BI Rate variable can be taken into consideration in determining investment strategies. An increase or decrease in interest rates greatly affects the economic condition of a country. For companies, analysis of microeconomic and macroeconomic factors is important in determining policy.